Effect of Low-Frequency Therapeutic Ultrasound on Induction of Nitric Oxide in CKD: Potential to Prevent Acute Kidney Injury - Michael W. Dae; Kathleen D. Liu; Richard J. Solomon; Dong W. Gao; Carol A. Stillson (Karger Publishers, 2020)
Introduction: Post-contrast acute kidney injury (PC-AKI) develops in a significant proportion of patients with CKD after invasive cardiology procedures and is strongly associated with adverse outcomes. Objective: We sought to determine whether increased intrarenal nitric oxide (NO) would prevent PC-AKI. Methods: To create a large animal model of CKD, we infused 250 micron particles into the renal arteries in 56 ± 8 kg pigs. We used a low-frequency therapeutic ultrasound device (LOTUS - 29 kHz, 0.4 W/cm2) to induce NO release. NO and laser Doppler probes were used to assess changes in NO content and blood flow. Glomerular filtration rate (GFR) was measured by technetium-diethylene-triamine-pentaacetic acid (Tc-99m-DTPA) radionuclide imaging. PC-AKI was induced by intravenous infusion of 7 cm3/kg diatrizoate. In patients with CKD, we measured GFR at baseline and during LOTUS using Tc-99m--DTPA radionuclide imaging. Results: In the pig model, CKD developed over 4 weeks (serum creatinine [Cr], mg/dL, 1.0 ± 0.2-2.6 ± 0.9, p < 0.01, n = 12). NO and renal blood flow (RBF) increased in cortex and medulla during LOTUS. GFR increased 75 ± 24% (p = 0.016, n = 3). PC-AKI developed following diatrizoate i.v. infusion (Cr 2.6 ± 0.7 baseline to 3.4 ± 0.6 at 24 h, p < 0.01, n = 3). LOTUS (starting 15 min prior to contrast and lasting for 90 min) prevented PC-AKI in the same animals 1 week later (Cr 2.5 ± 0.4 baseline to 2.6 ± 0.7 at 24 h, p = ns, n = 3). In patients with CKD (n = 10), there was an overall 25% increase in GFR in response to LOTUS (p < 0.01). Conclusions: LOTUS increased intrarenal NO, RBF, and GFR and prevented PC-AKI in a large animal model of CKD, and significantly increased GFR in patients with CKD. This novel approach may provide a noninvasive nonpharmacological means to prevent PC-AKI in high-risk patients.